Continuity and change: Negotiating gender norms in agricultural research for development in Rwanda - Rietveld, Anne M.; Farnworth, Cathy Rozel (International Maize and Wheat Improvement Center, 2018)
This resource is for research and development practitioners working in agriculture and rural development in Rwanda. The objective is to provide information about the ways in which gender norms in Eastern Rwanda are changing, and which ones remain persistent. It finds that despite broader institutional changes, men’s and women’s roles and relations in relation to farming, and the gender norms governing them, are changing in piecemeal ways.